EPIDEMIOLOGICAL ANALYSIS OF MENINGOCOCCAL INFECTION MORBIDITY IN THE REPUBLIC OF UZBEKISTAN (American Journal of Research in Humanities and Social Sciences, 2026)
This study presents a retrospective epidemiological analysis of meningococcal infection morbidity in the Republic of Uzbekistan. The aim of the study was to examine long-term trends in disease incidence as well as spatial patterns of its distribution across administrative territories. During the analysis, statistical data on registered cases of meningococcal infection throughout the country were reviewed, and temporal changes in incidence rates were assessed. The territorial analysis revealed elevated incidence levels in certain cities and districts, indicating an uneven spatial distribution of the epidemiological process.The findings demonstrate the dynamic character of the epidemiological situation with regard to meningococcal infection and persistently elevated morbidity in specific regions. This underscores the necessity of strengthening preventive measures and improving early case detection. The results are of practical importance for enhancing epidemiological surveillance and developing targeted prevention strategies for meningococcal infection.